Using Role Playing Activities to Improve Thai EFL Students’ Oral English Communication Skills - Suchada Tipmontree; Asama Tasanameelarp (International Journal of Business and Society, 2020)
The purposes of this study were to examine the effects of using role playing activities to enhance students speaking skills as well as to investigate the usefulness of role playing activities in the development of selfconfidencein oral English. The experiment was conducted with an intact group of 50 Thai EFL undergraduate students. The data were collected by using (1) the pre-speaking test and the post-speaking test on oral competence in English communication, (2) the assessment form on students’ self-confidence in speaking English, and (3) an interview form on students’ opinion and self-confidence in speaking English before and at the end of the course. The research results revealed that role playing activities had positive effects both on student’s oral competence and self-confidence in speaking English. The frequent practice over the period of time through the role playing activities is the vital key to enhance students’ speaking abilities and improve their speaking confidence.